2021
DOI: 10.3390/ijms221910691
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of PACAP in a Rat Model of Diabetic Neuropathy

Abstract: Pituitary adenylate cyclase-activating peptide (PACAP) is a neuropeptide with a widespread occurrence and diverse effects. PACAP has well-documented neuro- and cytoprotective effects, proven in numerous studies. Among others, PACAP is protective in models of diabetes-associated diseases, such as diabetic nephropathy and retinopathy. As the neuropeptide has strong neurotrophic and neuroprotective actions, we aimed at investigating the effects of PACAP in a rat model of streptozotocin-induced diabetic neuropathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 127 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…This has been demonstrated in numerous in vitro and in vivo studies (Reglodi et al 2011 , 2017 ). Recently, it has been shown that in addition to the long-known protective effects in models of stroke and Parkinson’s disease (Ohtaki et al 2008 ; Zheng et al 2021 ), PACAP is protective in models of spinal and bulbar muscular atrophy (Martinez-Rojas et al 2021 ), fetal alcohol syndrome (Shili et al 2021 ), diabetic neuropathy (Kiss et al 2021 ), optic neuritis in multiple sclerosis (Van et al 2021 ), and noise-induced hearing loss (Ruel et al 2021 ). The large body of evidence, showing that PACAP is protective in animal models of several diseases, places PACAP on the list of emerging protective therapeutic agents in neurodegenerative disorders (Cheng et al 2020 ; Soles-Tarres et al 2020 ) and stroke (Cherait et al 2021 ; Fang et al 2020 ; Sadanandan et al 2021 ; Zheng et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This has been demonstrated in numerous in vitro and in vivo studies (Reglodi et al 2011 , 2017 ). Recently, it has been shown that in addition to the long-known protective effects in models of stroke and Parkinson’s disease (Ohtaki et al 2008 ; Zheng et al 2021 ), PACAP is protective in models of spinal and bulbar muscular atrophy (Martinez-Rojas et al 2021 ), fetal alcohol syndrome (Shili et al 2021 ), diabetic neuropathy (Kiss et al 2021 ), optic neuritis in multiple sclerosis (Van et al 2021 ), and noise-induced hearing loss (Ruel et al 2021 ). The large body of evidence, showing that PACAP is protective in animal models of several diseases, places PACAP on the list of emerging protective therapeutic agents in neurodegenerative disorders (Cheng et al 2020 ; Soles-Tarres et al 2020 ) and stroke (Cherait et al 2021 ; Fang et al 2020 ; Sadanandan et al 2021 ; Zheng et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, intrathecal injection of PACAP38 during the acute phase of SNC attenuated mechanical allodynia and promoted axonal regeneration, indicating that Adcyap1 has significant implications for intraoperative intervention in PNI patients. Interestingly, PACAP38 has been identified as a promising therapeutic agent for diabetic neuropathy [ 56 ]. Overall, our findings suggest that Adcyap1 could potentially serve as an intrinsic protective factor promoting nerve regeneration and preventing pain during the acute phase after PNI.…”
Section: Discussionmentioning
confidence: 99%
“…All evaluations were recorded onto a computer using a Zeiss Axioscope II (Carl Zeiss Microscopy GmbH, Göttingen, Germany) microscope and photographed with a Zeiss Axiocam MRc camera attachment (Carl Zeiss MicroImaging GmbH, Göttingen, Germany). For transmission electron microscopic examinations, 50 nm ultra-fine sections were placed onto 200–300 mesh copper grids using a double contrast method by 2.5% uranyl–acetic acid and lead citrate [ 19 ]. The sections were then examined under a transmission electron microscope (JEOL-JEM-1010, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%